Population genomics uncover loci for trait improvement in the indigenous African cereal tef (Eragrostis tef) - Jones, R.W.M.; Kebede, Worku; Teshome, Abel; Girija, Aiswarya; Teshome, Adanech; Girma, Dejene; Brown, K. M. James; Quiroz-Chavez, Jesus; Jones, Christopher S.; Wulff, B. H. Brande; Assefa, Kebebew; Tadele, Zerihun; et al. (2024)
Tef (Eragrostis tef) is an indigenous African cereal that is gaining global attention as a gluten-free “superfood” with high protein, mineral, and fibre contents. However, tef yields are limited by lodging and by losses during harvest owing its small grain size (150x lighter than wheat). Breeders must also consider a strong cultural preference for white-grained over brown-grained varieties. Tef is relatively understudied with limited “omics” resources. Here, we resequenced 220 tef accessions from an Ethiopian diversity collection and also conducted multi-locational phenotyping for 25 agronomic and grain traits. Grain metabolome profiling revealed differential accumulation of fatty acids and flavonoids between white and brown grains. We conductedk-mer and SNP-based genome wide association and uncovered novel marker-trait associations. A significant 70 kb peak for panicle morphology contained the tef orthologue of riceqSH1, a transcription factor regulating inflorescence morphology in cereals. We also observed a previously unknown relationship between grain size, colour, and fatty acids. These traits were highly associated with retrotransposon insertions in homoeologues ofTRANSPARENT TESTA 2, a known regulator of grain colour. Our study provides valuable resources for tef research and breeding, facilitating the development of improved cultivars with desirable agronomic and nutritional properties.